2000
DOI: 10.1039/b002558p
|View full text |Cite
|
Sign up to set email alerts
|

The role of onium salts in the oxidation of hydrocarbons by O2 catalysed by cationic phase-transfer reagents

Abstract: Experimental and theoretical evidence is presented that cationic phase-transfer catalysts promote the homolytic decomposition of hydroperoxide initiators into radicals, this being a fundamental step in the catalysis of the oxidation of hydrocarbons bySuch decomposition of the model substance tert-butylwas found to have a value of 2, independently of the nature of the /*O 2 counteranion present. It is assumed that the interaction between hydroperoxide and onium cation is mainly electrostatic in nature and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…A further aerobic oxidation combines NHPI, xanthone and Me 4 NCl as a catalyst that warrants a fast decomposition of the alkylhydroperoxide 55. 56 Recently, a V‐catalyzed aerobic alkane oxidation using carboxylic acids and Eu(OTf) 3 as cocatalyst was reported 57…”
Section: Oxidation Of Non‐activated Sp3 Ch Bonds In Alkanes and Cmentioning
confidence: 99%
“…A further aerobic oxidation combines NHPI, xanthone and Me 4 NCl as a catalyst that warrants a fast decomposition of the alkylhydroperoxide 55. 56 Recently, a V‐catalyzed aerobic alkane oxidation using carboxylic acids and Eu(OTf) 3 as cocatalyst was reported 57…”
Section: Oxidation Of Non‐activated Sp3 Ch Bonds In Alkanes and Cmentioning
confidence: 99%
“…This result was consistent with other previous research. [18,28,29] What's more, radicals that formed by the homolytic activation of CHHP might be stabilized by BHT radical. The structures of the corresponding free radicals formed in chain initiation were studied by GC-MS preliminarily (Fig.…”
Section: Decomposition Proceduresmentioning
confidence: 99%
“…The ability of TOAB and of other onium salts to act as autoxidation initiators in the presence of hydroperoxides in apolar solvents was first recognized by Bredereck et al . and then confirmed by others . Kasaikina et al.…”
Section: Resultsmentioning
confidence: 95%
“…studied the decomposition of t BuOOH induced by surfactants and reported that the catalytic activities depend on the nature of both the cation and the counterion. With tetrahexylammonium salts, for instance, the efficiency was found to decrease in the order Br − >SCN − >Cl − >NO 3 − >ClO 4 − >F − . The activities of different ammonium ions, having Cl − as counterion, decreased in the order Hex 4 N + >BzBu 3 N + >MeOct 3 N + >Me 4 N + (Hex=hexyl, Bz=benzyl, Oct=octyl) .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation